Design Strategy of Talent Management in the Position of Non Management Staff PT XYZ - Gita Andini Siregar; Lindawati Kartika (Jurnal Manajemen Indonesia, 2020)
One of the biggest challenges of enterprise management is winning the talent war which is happens because the talent demanded is less than the talent needed. That is the reason that every company should develop and retain the talented employees to achieve business goals using a good talent management system. The aims of the research are to identify the implementation of talent management in PT XYZ through talent management factors and the determinant actors and to formulate the objective and strategy of talent management for PT XYZ. Data were analyzed using descriptive analysis and Analytical Hierarchy Process (AHP). Based on the descriptive analysis of PT XYZ employee perceptions of talent management criteria is considered good implementation. Based on Analytical Hierarchy Process (AHP) analysis, the most influential talent management factor is employee development, the most dominant talent management actor is the Manager, the most important objective is the nomination and selection of the employees from internal sources and the most influential alternative strategy of talent management is to make the Management as an instructor. Keywords—Analytical Hierarchy Process; Strategy; Talent management